2010
DOI: 10.2319/101909-584.1
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial growth in ectodermal dysplasia

Abstract: The deviation from normal facial growth of HED subjects tends to lessen with age. Functional and prosthetic appliances may have enhanced facial growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…1). One article had to be excluded or pooled with another because of possible double publication of the same cohort (Grecchi (b) [15]), one article because of missing follow-up times (Hvaring [16]), one because of missing clinical data (Kjaer [17]), and two articles because of missing numerical data (Dellavia [18, 19]). The study of Bergendal [20] could be kept in the analysis after contacting the author for clarification (no follow-up time reported).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). One article had to be excluded or pooled with another because of possible double publication of the same cohort (Grecchi (b) [15]), one article because of missing follow-up times (Hvaring [16]), one because of missing clinical data (Kjaer [17]), and two articles because of missing numerical data (Dellavia [18, 19]). The study of Bergendal [20] could be kept in the analysis after contacting the author for clarification (no follow-up time reported).…”
Section: Resultsmentioning
confidence: 99%
“…The two studies of Dellavia and coworkers [18, 19] contained drawings (polar diagrams) but not the underlying numerical data. Their evaluation of facial photographies demonstrated that patients with ectodermal dysplasia had a slightly reduced global facial growth in comparison with normal reference peers, with a delay of about 2 years in mandibular and maxillary peak developments.…”
Section: Resultsmentioning
confidence: 99%
“…Craniofacial and anthropometric changes are also described in XLHED and consist in reduced and retrognathic maxilla, frontal prominence, cranial base modifications, reduced facial convexity and facial height with deficiencies in sagittal and transverse skeletal growth (Johnson et al, 2002; Arslan et al, 2007; Clauss et al, 2008). Global reduction of facial growth, especially in the middle third of the facial skeleton, and mandibular growth retardation are integrated in HED craniofacial phenotype (Dellavia et al, 2010). Bone structural modifications have also been described in patients affected by XLHED and correspond to local increases of alveolar and basal bone densities and hypercorticalization (Lesot et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…All changes in the dental arches, including alveolar bone growth in response to tooth eruption, should be monitored to ensure appropriate adjustments are made. Long-term treatment is an active process that must be constantly adapted to the child's development and growth [10]. …”
Section: Discussionmentioning
confidence: 99%